Give Peace a Rating - eine vergleichende Analyse der Friedlichkeit der postsowjetischen Staaten - Netter, Lucas (2018)
Abstract: This study examines why some post-Soviet states are more peaceful than others. The analysis is conducted within the framework of a positivist, variable-based research design. The dependent variable is defined as the degree of peacefulness of the respective former Soviet Republics and measured by the Global Peace Index (investigation period: 2008-2017; Baltics excluded). Based on theoretical references, four independent variables are selected: (1) degree of democratization, (2) level of corruption, (3) stage of development, and (4) degree trade openness. The expected causal relationship between the explanatory factors and the phenomenon to be explained is formulated in the form of hypotheses: H 1: The higher the degree of democratization, the higher the degree of peacefulness (cases: Moldova; Turkmenistan). H 2: The lower the degree of corruption, the higher the degree of peacefulness (cases: Georgia; Turkmenistan). H 3: The higher the stage of development, the higher the degree of